Microbiological profile of transplant recipients in a tertiary care hospital in South India - Dr. Neelima. A; Dr. Umabala P.; Dr. M.A. Patil; Dr. Padmaja. K.; Dr. Sukanya.S.; Dr. Vijay Dharma Teja (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Infections are the leading cause of morbidity and mortality in transplant recipients. Advances in transplantation biology, organ procurement, surgical techniques, and immunosuppressive therapy have made organ transplantation an effective option for the management of organ failure, with a 1-year survival >60%-80%. However, infection remains one of the most challenging complications of transplantation. Materials & Methods: A total of 1156 clinical specimens from 300 patients who under-went solid organ (renal, liver, heart) & HSCT at Nizams Institute of Medical Sciences over a period of one year were included in the study. The specimens were investigated for microbiological staining, culture, antimicrobial susceptibility testing (AST) and Galactomannan (GM). Samples were processed as per the standard procedures. Results: Of the 1156 specimens received from Solid Organ Transplant/ Haematopoietic Stem Cell Transplant recipients, the majority were fromRenal transplant recipients (n= 1107, 95.76%) followed by HSCT (n=38, 3.28%). The rest were from recipients of liver (n=8), heart (n= 2) and heart- lung (n=1). About 63 showed growth on bacterial or fungal culture. SOT - 60 were culture positive, all were from renal transplant recipients. Most were UTI (n= 32, 53.3%) followed by Blood Stream Infection (n= 13, 21.6%). The other infections seen were pneumonia, wound infection.Of the bacterial isolates (n=49) gram negative- 40 (81.6%) gram positive- 9 (18.4%). E.coli was the predominant isolate (21, 52.5%). Drug resistance was seen in 19 isolates (38.77%), of which 6 were ESBL (31.5%), 13 multi drug resistant (68.4%). Mycobacteria- detected in 9 (n= 52 samples) of which 8 showed M. tuberculosis and one M. abscessus. MDRTB detected in 1 case. 9 patients were diagnosed with Probable Invasive Aspergillosis. Candida parapsilosis reported from a patient with sepsis.GMS stain showed P. carinii in one patient. HSCT-3 bacterial isolates were reported of which one strain was resistant to carbapenems. One Probable case of Invasive Aspergillosis reported. Conclusion: Urinary tract infections were predominant with most isolates multi drug resistance. Infection control measures should be used to decrease the incidence and bacterial resistance of infections.